Personality and Personality Disorders in Urban and Rural Africa: Results from a Field Trial in Burkina Faso - Rossier, Jérôme; Ouedraogo, Abdoulaye; Dahourou, Donatien; Verardi, Sabrina; Meyer de Stadelhofen, Franz (Frontiers in Psychology, 2013)
When conducting research in different cultural settings, assessing measurement equivalence is of prime importance to determine if constructs and scores can be compared across groups. Structural equivalence implies that constructs have the same meaning across groups, metric equivalence implies that the metric of the scales remains stable across groups, and full scale or scalar equivalence implies that the origin of the scales is the same across groups. Several studies have observed that the structure underlying both normal personality and personality disorders (PDs) is stable across cultures. Most of this cross-cultural research was conducted in Western and Asian cultures. In Africa, the few studies were conducted with well-educated participants using French or English instruments. No research was conducted in Africa with less privileged or preliterate samples. The aim of this research was to study the structure and expression of normal and abnormal personality in an urban and a rural sample in Burkina Faso. The sample included 1,750 participants, with a sub-sample from the urban area of Ouagadougou (n = 1,249) and another sub-sample from a rural village, Soumiaga (n = 501). Most participants answered an interview consisting of a Mooré language adaptation of the Revised NEO Personality Inventory and of the International Personality Disorders Examination. Mooré is the language of the Mossi ethnic group, and the most frequently spoken local language in Burkina Faso. A sub-sample completed the same self-report instruments in French. Demographic variables only had a small impact on normal and abnormal personality traits mean levels. The structure underlying normal personality was unstable across regions and languages, illustrating that translating a complex psychological inventory into a native African language is a very difficult task. The structure underlying abnormal personality and the metric of PDs scales were stable across regions. As scalar equivalence was not reached, mean differences cannot be interpreted. Nevertheless, these differences could be due to an exaggerated expression of abnormal traits valued in the two cultural settings. Our results suggest that studies using a different methodology should be conducted to understand what is considered, in different cultures, as deviating from the expectations of the individual’s culture, and as a significant impairment in self and interpersonal functioning, as defined by the DSM-5.